Aplicação da lei Maria da Penha à luz da perspectiva gênerosensitiva: o acesso à justiça da mulher vítima de violência doméstica em João Pessoa/PB. - Bezerra, Higyna Josita Simoes de Almeida (2011)
Despite all the accomplishments reached by women in public services, they still are very vulnerable to domestic violence in their own place. Having the need of facing this problem, one of the ways pointed by Law was the creation of law 11.323/2006 as a way to compensate them for the suffered discrimination since the domestic violence is one of the expressions of the patriarchal power and the women´s subordination situation in society. However, the formal existence of the law does not guarantee that the victim of domestic violence have effective access to justice neither that transformations of gender hierarchical relations will occur. In the following work, we start from the hypotheses that the interpretation/application of the Maria da Penha Law in the light of the sensitive-gender perspective will make the access to justice easier to victims of domestic violence because this scope takes into consideration that this violence is a product of the gender patriarchal system and is generated by a cultural thought that establishes unequal parts of power in detriment to women, putting her in an inferior position in relation to men, being an instrument of reproduction/maintenance of male domination. The following study aims at investigating the work of criminal judges in João Pessoa court district in 2009, trying to know if law 11.340/2006 was interpreted and applied in such a way to facilitate the access to justice for women victims of domestic violence. It was done through empirical research in the 2009 sentence register books from the criminal lower courts in João Pessoa, state capital of Paraiba, with the help of a semistructured instrument of research, having come to conclusion that the decisions were made, in most of times, without having effective contribution to the right of women to have a life free of violence. By not associate the juridical field to the social one, the Judicial System ended up applying Maria da Penha Law incorporating the practical side of it and no the political one, confirming the androcentric aspect of Law and stimulating the reprivatization of the conjugal domestic conflict.